An analytical study for global buckling of circular tubes under axial and oblique compression. (June 2017) - Wang, Wei; Qiu, XinMing
Abstract: An analytical model is proposed for global buckling circular tubes of low diameter-to-thickness ratio ( 25 < D / t < 40 ) and moderate length ( 7 < L / D < 8 ), based on experimental observations and numerical simulations. Compared with FEM simulations, the current model gives accurate predictions on the whole load-displacement curve, energy dissipation and peak force. Employing this model, the energy absorption properties of circular metal tubes are analyzed. For global buckling tubes of same geometry, fixed boundary can absorb more energy than free boundary due to the bending plastic mechanism at ends. For oblique compression (compression angle ≤ 30 ° ), the load-displacement curve of global buckling is similar to that of uniaxial compression. For tubes of different geometries under uniaxial compression, the total response and energy absorption ability are compared between global buckling and progressive buckling. If the effective stoke is small, the specific energy absorbing (SEA) of global buckling tube could be higher than progressive buckling tube. Highlights: An analytical model is proposed for global buckling circular tubes. Current predictions of load-displacement curve, energy dissipation agree well with FE simulations. The response of oblique compression (angle ≤ 30 ° ) is similar to that of un-axial compression. Response of global buckling and progressive buckling are compared for un-axial compression tubes.